Colonic and type IV jejunal atresias with apple-peel bowel segment as the content of right inguinal hernia: A case report - Deepa P Makhija; Abhijit Kumar; Rahul K Gupta; Beejal V Sanghvi; Kedar P Mudkhedkar; Rujuta S Shah; Manish P Khobragade; Sandesh V Parelkar (EL-Med-Pub, 2021)
Background: Colonic atresia is an uncommon entity. It may be associated with multiple anomalies. Case Presentation: We present a case, which was initially suspected to be jejunal atresia, but was found to have colonic atresia as well intra-operatively. The associated jejunal atresia with apple-peel configuration was present as the content of inguinal hernia. Conclusion: This case report highlights the rarity of the condition and the postoperative issues in the management of such patients.